Inside star vision planetary awakening and self-transformation - Lonsdale, Ellias 1947-; Lonsdale, Theanna -1993 (Spirit). (Berkeley, California North Atlantic Books, 2000)
Inside Star Vision is a landmark astrology book for the twenty-first century and centuries to come. It views human destiny and the life and death travels of individual souls as part of the larger journey undertaken by the universe itself in various modes of being and intelligence. Lonsdale not only leads us through signs, houses, and planets, but also interprets them in the context of broader archetypes and vision quests. He delineates the years 2000, 2001, 2002, 2003, 2004, 2005, and 2006, and in a daring and profound act of spiritual writing, he sets the cosmic terms for the imminent transformation of humanity through an opening of the door between the two most separated realms of all, life and death.
Keywords: Astrology; Self-actualization (Psychology) -- Miscellanea